Sox2 Suppression by miR‐21 Governs Human Mesenchymal Stem Cell Properties. (4th December 2013) - Trohatou, Ourania; Zagoura, Dimitra; Bitsika, Vasiliki; Pappa, Kalliopi I.; Antsaklis, Aristidis; Anagnou, Nicholas P.; Roubelakis, Maria G.
Abstract : The miRNA profile of mesenchymal stem cells (MSCs) derived from amniotic fluid, bone marrow (BM), and umbilical cord blood was analyzed. Initially, 67 different miRNAs were identified that were expressed in all three types of MSCs but at different levels, depending on the source. A more detailed analysis revealed that miR‐21 was expressed at higher levels in RS‐AF‐MSCs and BM‐MSCs compared with SS‐AF‐MSCs. Findings suggest that miR‐21 might function by regulating Sox2 expression in human MSCs and might also act as a key molecule determining MSC proliferation and differentiation. Abstract : MicroRNAs (miRNAs) have recently been shown to act as regulatory signals for maintaining stemness and for determining the fate of adult and fetal stem cells, such as human mesenchymal stem cells (hMSCs). hMSCs constitute a population of multipotent stem cells that can be expanded easily in culture and are able to differentiate into many lineages. We have isolated two subpopulations of fetal mesenchymal stem cells (MSCs) from amniotic fluid (AF) known as spindle‐shaped (SS) and round‐shaped (RS) cells and characterized them on the basis of their phenotypes, pluripotency, proliferation rates, and differentiation potentials. In this study, we analyzed the miRNA profile of MSCs derived from AF, bone marrow (BM), and umbilical cord blood (UCB). We initially identified 67 different miRNAs that were expressed in all three types of MSCs but at different levels, depending on the source. A more detailed analysis revealed that miR‐21 was expressed at higher levels in RS‐AF‐MSCs and BM‐MSCs compared with SS‐AF‐MSCs. We further demonstrated for the first time a direct interaction between miR‐21 and the pluripotency marker Sox2. The induction of miR‐21 strongly inhibited Sox2 expression in SS‐AF‐MSCs, resulting in reduced clonogenic and proliferative potential and cell cycle arrest. Strikingly, the opposite effect was observed upon miR‐21 inhibition in RS‐AF‐MSCs and BM‐MSCs, which led to an enhanced proliferation rate. Finally, miR‐21 induction accelerated osteogenesis and impaired adipogenesis and chondrogenesis in SS‐AF‐MSCs. Therefore, these findings suggest that miR‐21 might specifically function by regulating Sox2 expression in human MSCs and might also act as a key molecule determining MSC proliferation and differentiation.